(untitled) (Eurasian Journal of Philology Science and Education, 2022)
All inventions of mankind, from primitive tools to modern sophisticated technologies demonstrate the need of their creators for a figurative understanding of the spiritual world and visual display of abstract concepts generated by consciousness. This is evidenced by the ancient tamga signs carved in stone. Today we can quite consider tamga signs as works of ancient art, despite their primary functional purpose associated with a symbolic impact on nature. Even in the era of antiquity, the theory proposed by Aristotle substantiated that art is born from imitation of nature. The aim of this article is to determine the sacred meanings of the ancient generic signs of Mangistau, and the functional features of the sacred space. Most of them have survived in the form of petroglyphs and tamga signs carved on tombstones, sandyktas, sarcophagi of antiquity in the Middle Ages, as well as on the walls of saganatams and domed mausoleums of a later period. There are also preserved tamgas, carved on large boulders and rocks. In the course of the research, the symbolic meanings of the ancient Oguz tamga signs of Mangystau were substantiated through conceptual and semantic analyses. A comparative analysis of information from a number of scientific studies about ancient symbols has been carried out. As a result of the study, an assumption was made about the following issues: existence in nature of generic signs of conceptual meanings; the sacraments of life; the universe; belonging, generic markings; state symbols; pilgrimage presences and the location of burial. Key words: tamga, oguz, conceptual, sacred, property, gravestones.